Knowledge Production in Continuing Teacher Education: Epistemological and Methodological Contributions for Its Inquiry - Mariana Carballo (Perspectivas Metodológicas​)
This article presents an area that has barely been explored until now: the production of knowledge on Continuing Teacher Training in Argentina. To this end, a synthesis of the main conceptual delimitations for its approach is presented. Firstly, the need for this type of studies and the contributions of research on the state of the art are justified. Secondly, the methodology used, the instruments and the dimensions of analysis are specified. Thirdly, the theoretical foundations of the epistemological-methodological approaches for addressing the production of knowledge on Continuing Teacher Training are expressed. As conclusions, a final section of discussions and challenges is included.